Associations between Organ Dysfunction Scoring Systems and Dysregulated Host Responses in Adults with Severe Infection in Uganda: A Prospective Cohort Study - Tiao, Jonathan; Bakamutumaho, Barnabas; Owor, Nicholas; Kayiwa, John; Namulondo, Joyce; Byaruhanga, Timothy; Muwanga, Moses; Nsereko, Christopher; Nayiga, Irene; Che, Xiaoyu; Lipkin, W Ian; Lutwama, Julius J; et al. (The American journal of tropical medicine and hygiene, 2025)
Scoring systems for organ dysfunction (e.g., the quick Sepsis-related Organ Failure Assessment [qSOFA], Modified Early Warning Score [MEWS], and Universal Vital Assessment [UVA]) are proposed as clinical criteria for sepsis. The content validity of these scoring systems is poorly understood in sub-Saharan Africa, where the global sepsis burden is concentrated. In a prospective cohort of 288 adults hospitalized with suspected sepsis in Uganda, we show that qSOFA, MEWS, and UVA scores were significantly associated with soluble mediators of innate and adaptive immune activation, endothelial dysfunction, and fibrinolysis. Results were consistent after adjustment for demographics, illness duration, and HIV or malaria coinfection. In resource-limited settings in sub-Saharan Africa, organ dysfunction scores may stratify patients at highest risk of poor outcomes and those with more dysregulated host responses. Further studies are needed to better define these relationships, including the temporal dynamics of dysregulated host responses and organ dysfunction in sepsis.